The relationship between dental status, food selection, nutrient intake, nutritional status, and body mass index in older people - Wagner Marcenes; Jimmy George Steele; Aubrey Sheiham; Angus Willian Gilmour Walls
This paper reviewed the findings from a national survey in Great Britain which assessed whether dental status affected older people's food selection, nutrient intake, and nutritional status. The survey analyzed national random samples of free-living and institution subjects for dental examination, interview, and four-day food diary as well as blood and urine tests In the free-living sample, intakes of non-starch polysaccharides, protein, calcium, non-heme iron, niacin, and vitamin C were significantly lower in edentulous as compared to dentate subjects. People with 21 or more teeth consumed more of most nutrients, particularly non-starch polysaccharides. This relationship in intake was not apparent in the hematological analysis. Plasma ascorbate and retinol were the only analytes significantly associated with dental status. Having 21 or more teeth increased the likelihood of having an acceptable body mass index (BMI). Thus, maintaining a natural and functional dentition defined as having more than twenty teeth into old age plays an important role in having a healthy diet rich in fruits and vegetables, a satisfactory nutritional status, and an acceptable BMI.